Becoming after College: Agency and Structure in Transitions to Engineering Work. Issue 2 (4th May 2021) - Gewirtz, Chris; Paretti, Marie C.
Abstract : Engineering education and engineering studies research has clearly articulated a need for educational reform to help new engineers understand social dimensions of their work and act as change agents. At the same time, while some practicing engineers may be committed to systemic change and service to society, they must also contend with work responsibilities which serve corporate interests and constrain change. To highlight tensions between calls for socially just engineering education and the corporate contexts constraining engineering work, this study examines the transition to work for one early career engineer. Drawing on the concept of figured worlds, we examine the under-explored relationship between the agency of individual engineers and the structure of engineering workplace culture. This structure-agency approach guides our narrative analysis of the participant's early work experience based on five interviews across her first two years of work. Our findings illustrate the need to extend representations of both educational preparation and engineering work by unpacking the complex identity negotiations that individuals experience. In doing so, we also demonstrate the value of both the structure-agency framework and narrative methods for identity researchers in both engineering studies and engineering education.